Coronary stent CD31-mimetic coating favours endothelialization and reduces local inflammation and neointimal development in vivo - Diaz-Rodriguez, Sergio (Eur Heart J, 2021)
AIMS: The rapid endothelialization of bare metal stents (BMS) is counterbalanced by inflammation-induced neointimal growth. Drug-eluting stents (DES) prevent leukocyte activation but impair endothelialization, delaying effective device integration into arterial walls. Previously, we have shown that engaging the vascular CD31 co-receptor is crucial for endothelial and leukocyte homeostasis and arterial healing. Furthermore, we have shown that a soluble synthetic peptide (known as P8RI) acts like a CD31 agonist. The aim of this study was to evaluate the effect of CD31-mimetic metal stent coating on the in vitro adherence of endothelial cells (ECs) and blood elements and the in vivo strut coverage and neointimal growth. METHODS AND RESULTS: We produced Cobalt Chromium discs and stents coated with a CD31-mimetic peptide through two procedures, plasma amination or dip-coating, both yielding comparable results. We found that CD31-mimetic discs significantly reduced the extent of primary human coronary artery EC and blood platelet/leukocyte activation in vitro. In vivo, CD31-mimetic stent properties were compared with those of DES and BMS by coronarography and microscopy at 7 and 28 days post-implantation in pig coronary arteries (n = 9 stents/group/timepoint). Seven days post-implantation, only CD31-mimetic struts were fully endothelialized with no activated platelets/leukocytes. At day 28, neointima development over CD31-mimetic stents was significantly reduced compared to BMS, appearing as a normal arterial media with the absence of thrombosis contrary to DES. CONCLUSION: CD31-mimetic coating favours vascular homeostasis and arterial wall healing, preventing in-stent stenosis and thrombosis. Hence, such coatings seem to improve the metal stent biocompatibility.